The Value of Ultrasound in Diagnosing Acute Appendicitis - Mushref Abdulsalam, Baha'a (Tikrit Journal of Pharmaceutical Sciences, 2023)
Acute appendicitis considered one of the causes of acute abdomen. The diagnosis is usually straight forward in typical cases, but this is not true in atypical cases. This study is to assess the value of ultrasound modality in diagnosing acute appendicitis. From January 2009 to January 2012 in Al-Ramadi teaching hospital, 196 patients were included in this study, 10 patients were excluded, and 186 examined by ultrasound, after adequate clinical assessment, for their signs and symptoms that suggestive of acute appendicitis. Age groups were 6-75 years, Mean age 33.5 years, with 105(54%) males, and 91(46%) females. 186 patients could be explained, and examined by ultrasound, with mean age of 33.5 years, the diagnosis had established in 34 patients. The false positive was three cases, and false negative was six cases, this means that the ultrasound had failed in these nine cases. The sensitivity is 81.8%, the specificity is 98%. 90% and 96.2% are the positive and negative predictive values respectively. The diagnostic accuracy is 95.5%. The P-value is